SARS-CoV-2 Receptor Angiotensin I-Converting Enzyme Type 2 (ACE2) Is Expressed in Human Pancreatic β-Cells and in the Human Pancreas Microvasculature - Fignani, Daniela; Licata, Giada; Brusco, Noemi; Nigi, Laura; Grieco, Giuseppina E.; Marselli, Lorella; Overbergh, Lut; Gysemans, Conny; Colli, Maikel L.; Marchetti, Piero; Mathieu, Chantal; Eizirik, Decio L.; et al. (Frontiers in Endocrinology, 2020)
Increasing evidence demonstrated that the expression of Angiotensin I-Converting Enzyme type 2 (ACE2), is a necessary step for SARS-CoV-2 infection permissiveness. In the light of the recent data highlighting an association between COVID-19 and diabetes, a detailed analysis aimed at evaluating ACE2 expression pattern distribution in human pancreas is still lacking. Here, we took advantage of INNODIA network EUnPOD biobank collection to thoroughly analyse ACE2, both at mRNA and protein level, in multiple human pancreatic tissues and using several methodologies. Using multiple reagents and antibodies, we showed that ACE2 is expressed in human pancreatic islets, where it is preferentially expressed in subsets of insulin producing β-cells. ACE2 is also is highly expressed in pancreas microvasculature pericytes and moderately expressed in rare scattered ductal cells. By using different ACE2 antibodies we showed that a recently described short-ACE2 isoform is also prevalently expressed in human β-cells. Finally, using RT-qPCR, RNA-seq and High-Content imaging screening analysis, we demonstrated that pro-inflammatory cytokines, but not palmitate, increases ACE2 expression in the β-cell line EndoC-βH1 and in primary human pancreatic islets. Taken together, our data indicate a potential link between SARS-CoV-2 and diabetes through putative infection of pancreatic microvasculature and/or ductal cells and/or through direct β-cell virus tropism.